Effect of Daily Consumption of Lactobacillus reuteri CRL 1098 on Cholesterol Reduction in Hypercholesterolemic Subjects - Malpeli, Agustina (2015)
The effect of daily consumption of a yogurt containing Lactobacillus reuteri CRL 1098 on the lipid profile of hypercholesterolemic subjects was evaluated by performing a prospective, randomized, double-blind, cross-over placebo controlled clinical study. Participants consumed daily a yogurt containing L. reuteri CRL 1098 or a placebo for four weeks, separated by a wash-out period. Total cholesterol, triacylglycerol, high-density (HDL) and low-density (LDL) lipoprotein levels were assessed at the beginning and at the end of each period. We found a statistically significant reduction of total (−7.86 g/dl) and LDL (−7.02 g/dl) cholesterol in absolute changes (before-after) as well as a decreasing trend in the group receiving the yogurt containing L. reuteri with respect to the placebo group, without detecting changes in HDL-cholesterol and triacylglycerol levels. Our results suggest that low amounts of yogurt (125 g/day) and low doses of the CRL 1098 strain (106 CFU) are sufficient to reduce total and LDL-cholesterol levels in hypercholesterolemic subjects.